2010
DOI: 10.1177/193229681000400605
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Native Glucagon Sequence for Medicinal Purposes

Abstract: Background: Glucagon is a life-saving medication used in the treatment of hypoglycemia. It possesses poor solubility in aqueous buffers at or near physiological pH values. At low and high pH, at which the peptide can be formulated to concentrations of a milligram or more per milliliter, the chemical integrity of the hormone is limited, as evidenced by the formation of multiple degradation-related peptides. Consequently, the commercial preparation is provided as a lyophilized solid with an acidic diluent and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 23 publications
5
87
0
Order By: Relevance
“…Investigation of chimeric receptor activation by hybrid peptides showed that, like Glucagon Like Peptide-1 (GLP-1) and Gastric Inhibitory Peptide (GIP) [22,31,42], the glucagon carboxyl-terminal half is anchored on the receptor extracellular Nterminal domain, and the receptor is activated by the interaction of the amino-terminal half of the peptide with the transmembrane domain [30,32,39]. This conclusion has been supported by several other studies: glutamate 68 in the GLP-1 receptor N-terminal domain (replaced by K64 in the glucagon receptor) reduces the GLP-1 receptor affinity for glucagon by charge repulsion with its' C-terminal carboxyl [4,8]; an aspartate (D385, replaced by E387 in the GLP-1 receptor) in TM7 is responsible for preferential recognition of the glucagon S2 over GLP-1 A2; K187 and I194 side chains in TM2 participate in the preference for glucagon Q3 [24,30] over GLP-1 E3; and unidentified side chains in ECL2, for glucagon K12 [30].…”
Section: Abbreviationsmentioning
confidence: 61%
“…Investigation of chimeric receptor activation by hybrid peptides showed that, like Glucagon Like Peptide-1 (GLP-1) and Gastric Inhibitory Peptide (GIP) [22,31,42], the glucagon carboxyl-terminal half is anchored on the receptor extracellular Nterminal domain, and the receptor is activated by the interaction of the amino-terminal half of the peptide with the transmembrane domain [30,32,39]. This conclusion has been supported by several other studies: glutamate 68 in the GLP-1 receptor N-terminal domain (replaced by K64 in the glucagon receptor) reduces the GLP-1 receptor affinity for glucagon by charge repulsion with its' C-terminal carboxyl [4,8]; an aspartate (D385, replaced by E387 in the GLP-1 receptor) in TM7 is responsible for preferential recognition of the glucagon S2 over GLP-1 A2; K187 and I194 side chains in TM2 participate in the preference for glucagon Q3 [24,30] over GLP-1 E3; and unidentified side chains in ECL2, for glucagon K12 [30].…”
Section: Abbreviationsmentioning
confidence: 61%
“…Collectively, these nonglycemic effects render glucagon an interesting candidate for pharmacological management of body weight. However, beyond the central dilemma of its diabetogenic liability resides the fact that glucagon is poorly suited as a drug substance, given its short duration of action, poor aqueous solubility, and chemical stability at physiologic pH (Gratzer et al, 1972;Chabenne et al, 2010). The solubility of glucagon in physiologic buffer can be dramatically improved by extension of its sequence at the C terminus with the CEX terminal end of exendin-4 Chabenne et al, 2010).…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 99%
“…However, beyond the central dilemma of its diabetogenic liability resides the fact that glucagon is poorly suited as a drug substance, given its short duration of action, poor aqueous solubility, and chemical stability at physiologic pH (Gratzer et al, 1972;Chabenne et al, 2010). The solubility of glucagon in physiologic buffer can be dramatically improved by extension of its sequence at the C terminus with the CEX terminal end of exendin-4 Chabenne et al, 2010). Chronic s.c. infusion of DIO mice with glucagon-CEX in physiologic buffer improved body weight and glycemic control with equal efficacy when compared with equimolar administration of exendin-4 .…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 99%
“…It should be noted that prolonged glucagon infusion might require use of a new formulation or analog molecule to avoid fibrillation. 16 The use of such a drug in a clinical trial would have to be cleared by a joint process involving two FDA centers, the CDRH and the CDER. Although the panel endorsed the idea of "one size will not fit all," which means that various patients will require various protocols and outcomes, this diversity of outcomes might be achievable with a limited number of products or tools that can be calibrated to the needs of the individual patient.…”
Section: Discussion Of Clinical Expectations For Artificial Pancreas mentioning
confidence: 99%